2017
DOI: 10.21315/mjms2017.24.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rotavirus Strains Causing Diarrhoea in Children under Five Years of Age in Yogyakarta, Indonesian

Abstract: Background: Rotavirus is an important cause of severe diarrhoea in children. The aims of this study were to identify the rotavirus strains that cause diarrhoea in children in Yogyakarta and to determine the association between rotavirus positivity and its clinical manifestations.Methods: Clinical data and stool samples were collected from children hospitalised at Kodya Yogyakarta Hospital, Indonesia. Rotavirus was detected in stool samples using an enzyme immunoassay (EIA), which was followed by genotyping usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 37 publications
4
14
0
2
Order By: Relevance
“…Our study showed that the largest group of patients comprise of children between 2 and 5 years of age and this finding is consistent with other study results (17,19,20). Also in line with other studies, the incidence of AGE in boys was slightly higher than in girls (21,22).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study showed that the largest group of patients comprise of children between 2 and 5 years of age and this finding is consistent with other study results (17,19,20). Also in line with other studies, the incidence of AGE in boys was slightly higher than in girls (21,22).…”
Section: Discussionsupporting
confidence: 93%
“…The correlations between clinical signs and etiological factors in this study were consistent with other results (17,20,26,27). Fever, diarrhea and stools with blood, mucus and/or pus occurred more frequent in patients with bacterial AGE, while vomiting appeared more often in children with viral infections.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Full genome analysis on the Indonesia G3P[8] strain demonstrated it was an inter-genogroup reassortant, containing an equine-like G3 VP7, a P[8] VP4 gene and a genogroup 2 backbone I2-R2-C2-M2-A2-N2-T2-E2-H2. This strain has not been previously reported in strain surveillance conducted in Indonesia [29] , [30] . The genomes of the Indonesian equine-like G3P[8] strains were most similar to strains detected in Spain and Hungry in 2015 [31] , [32] .…”
Section: Discussionmentioning
confidence: 71%